University youth and online safety in Egypt: use and trust - Alsherif, Nasser (AUC Knowledge Fountain, 2014)
The Internet contributes significantly to the positive development of humanity. That being said, Internet accessibility presents a possibility for exposure to harmful content or interaction, specifically to young minds. This study aims at investigating how youth use the Internet in the context of Online Safety. It examines uses and gratifications of the Internet and trust levels of Internet Safety. Moreover, it attempts to explore the risks that could be faced online. A survey was conducted on a convenience sample of 402 University Youth students. The results of the study revealed that respondents use the Internet mainly to satisfy their interpersonal utility needs. It also suggests that they have high trust levels of the safety of certain online practices.